2014
DOI: 10.1016/j.visres.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Salient stimulus attracts focus of peri-saccadic mislocalization

Abstract: Visual localization during saccadic eye movements is prone to error. Flashes shortly before and after the onset of saccades are usually perceived to shift towards the saccade target, creating a “compression” pattern. Typically, the saccade landing point coincides with a salient saccade target. We investigated whether the mislocalization focus follows the actual saccade landing point or a salient stimulus. Subjects made saccades to either a target or a memorized location without target. In some conditions, anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…We have shown previously that saccades which are performed “into the void” without the presentation of a saccade target do not induce perisaccadic compression (Zimmermann et al, 2014c ). Similarly, Luo et al ( 2014 ) observed reduced compression magnitudes when no saccade target was presented. We also observed absence of compression during the second saccade of a double-step saccade sequence, where the first saccade was in vertical and the second saccade in horizontal direction (Zimmermann et al, 2014b ).…”
Section: Discussionmentioning
confidence: 77%
“…We have shown previously that saccades which are performed “into the void” without the presentation of a saccade target do not induce perisaccadic compression (Zimmermann et al, 2014c ). Similarly, Luo et al ( 2014 ) observed reduced compression magnitudes when no saccade target was presented. We also observed absence of compression during the second saccade of a double-step saccade sequence, where the first saccade was in vertical and the second saccade in horizontal direction (Zimmermann et al, 2014b ).…”
Section: Discussionmentioning
confidence: 77%
“…Such relationships occur only with connected content. There are numerous examples of distorted spatial relationships under various conditions such as perisaccadic mislocalization 81 and compression 82 and with numerous spatial illusions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, Zimmermann et al ( 2014b ) have recently shown that saccadic compression is greatly diminished when no visual reference is presented in the visual field, but saccades are directed towards the empty screen center. Compression re-emerged when irrelevant visual reference stimuli were presented, albeit with attraction towards the reference, not the saccade endpoint at the center of the screen (see also Cicchini et al, 2013 ; Luo et al, 2014 ). These findings suggest that even in saccadic compression, strong visual signals may override weaker extra-retinally generated signals to act as attractors (see also Lappe and Hamker, 2015 , this issue).…”
Section: Discussionmentioning
confidence: 99%
“…Given the retinotopic organization of many cortical areas, spatial updating of retinotopic coordinates across eye movements is clearly required. However, we suggest that compression effects (although certainly being very striking phenomena and interesting to study in their own right) may not be related to these updating processes, as they also occur in situations in which no spatial updating is needed such as mask-induced compression or motion-induced compression (see also Ostendorf et al, 2006 ; Shim and Cavanagh, 2006 ) and they are greatly reduced when spatial updating is needed but no visual reference is available (Luo et al, 2014 ; Zimmermann et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%